2018
DOI: 10.3390/rs10010122
|View full text |Cite|
|
Sign up to set email alerts
|

Determining the Start of the Growing Season from MODIS Data in the Indian Monsoon Region: Identifying Available Data in the Rainy Season and Modeling the Varied Vegetation Growth Trajectories

Abstract: Abstract:In the Indian monsoon region, frequent cloud cover in the rainy season results in less valid satellite observations during the vegetation growth period, making it difficult to extract land surface phenology (LSP). Even worse, many valid but humid observations were misidentified as clouds in the MODIS cloud mask, causing severe gaps in the LSP product. Using a refined cloud detection approach to separate clear-sky and cloudy observations, this study found that potentially valid observations during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The difference between histogram dispersals of phenological metrics of estimated VIs may be due to their varying sensitivities to soil context variations. Likewise, in the drylands of Arizona, USA, the spatiotemporal variability of soil surface phenology removed from NDVI was higher than EVI [61]. The difference in highest greenness between NDVI and EVI was related to the physiological features of the vegetation types due to their different sensitivities [36].…”
Section: Detection Of Phenology Metricsmentioning
confidence: 93%
“…The difference between histogram dispersals of phenological metrics of estimated VIs may be due to their varying sensitivities to soil context variations. Likewise, in the drylands of Arizona, USA, the spatiotemporal variability of soil surface phenology removed from NDVI was higher than EVI [61]. The difference in highest greenness between NDVI and EVI was related to the physiological features of the vegetation types due to their different sensitivities [36].…”
Section: Detection Of Phenology Metricsmentioning
confidence: 93%
“…The accuracy of cloud masks is critical to minimise errors in processing of time series data from satellites. Faulty cloud masks have been shown to deviate the estimated start of season by up to 10 days [142] and hence require careful consideration in modelling of vegetation index time series curves. This is particularly important for the Sentinel-2 dataset, since Pastick et al (2018) [62] showed that the cloud masks available with the HLS, which uses the popular LaSRC and Fmask algorithms, were of poor quality (accuracy of 76-89%) and had to be recalculated from Landsat-8 and Sentinel 2 data using decision trees (yielding an accuracy of 99%).…”
Section: Overcoming Cloud Covermentioning
confidence: 99%
“…The Moderate Resolution Imaging Spectroradiometer (MODIS) remote sensing data provide the possibility to monitor vegetation phenology and have been increasingly used for monitoring vegetation phenology (Zhang et al, 2004;Wang et al, 2015b;Shang et al, 2018). MODIS sensors aboard Terra and Aqua satellites have been in operation since 1999 and 2002, respectively, and can provide long-term remote sensing NDVI and enhanced vegetation index (EVI) records of >10 years (Wang et al, 2021;Zhu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%